Computer Systems Digital Design, Fundamentals of Computer Architecture and Assembly Language - Elahi, Ata.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. •  Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly •  Covers basic number system and coding, basic knowledge in digital design, and components of a computer •  Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter        .
Introduction -- Information Representation in Computer -- Boolean Algebra and Logic Gates -- Combination Logic -- Sequential Logic -- Fundamentals Computer Architecture -- Memory -- Input / Output -- Pipelining and CPU Performance -- ARM Architecture and Instructions -- ARM Assembly Language Programming Using Kiel Development Tools -- Conclusion.
Keywords: Telecommunication; Electronic circuits; Computer networks .; Microprocessors; Computer architecture; Coding theory; Information theory; Communications Engineering, Networks; Electronic Circuits and Systems; Computer Communication Networks; Processor Architectures; Coding and Information Theory